Dampak Moderasi Budaya Catur Purusa Artha pada Pengaruh Self Efficacy dan Locus of Control terhadap Kinerja Koperasi - Eka Saputra, I Gede Hendra; Yasrawan, Komang Tri (Universitas Pendidikan Ganesha, 2021)
This research was conducted to find out the effect of self-efficacy and locus of control on performance as moderated by the Purusha Arta Chess Culture. This type of research is included in quantitative research with a causal or causal approach. The research sample was 80 respondents with a research instrument using a questionnaire. Methods of data analysis in this study using Structural Equation Modeling Partial Least Square (SEM PLS). The results show that self-efficacy and locus of control have a positive effect on cooperative performance and the existence of Catur Purusa Artha (CPA) is able to influence the effect of self-efficacy on performance, but CPA is unable to moderate the effect of locus of control on performance. This research has contributed in providing awareness to cooperative administrators about several factors that can help improve performance amid the Covid-19 pandemic.